A qualitative study examining prosthesis use in everyday life in individuals with lower limb amputations. Issue 4 (23rd August 2021) - Roberts, Evan; Burhani, Lamya; Lankester, Ryan; Mobbs, Alexander; Tigert, Carly; Vanvelzen, Troy; Campbell, Janet; Devlin, Michael; Dilkas, Steven; MacKay, Crystal
Abstract : Background: Lower limb amputation (LLA) is a life-changing event that affects functional mobility and participation in everyday life. Prostheses provide individuals with LLA the opportunity to improve mobility and quality of life; however, existing literature suggests that there is underuse of prostheses. Objectives: The purpose of this study is to describe how individuals with major LLA use their prosthesis in everyday life and describe barriers and facilitators that influence prosthesis use. Study Design: A qualitative descriptive methodology was used. Methods: Ten community dwelling adults (>18 years) with unilateral major LLAs (transtibial, transfemoral, and knee disarticulation) attending outpatient follow-up at a specialized rehabilitation center were recruited. Participants were purposively sampled for variation in prosthesis use and level of amputation. One-on-one semistructured in-depth interviews were conducted in person or by telephone. The interviews were audio recorded, transcribed verbatim, and analyzed inductively using thematic analysis. Results: The experiences of individuals with major LLA were organized into three overarching themes: everyday experiences using a prosthesis, extrinsic factors influencing prosthesis use, and intrinsic factors influencing prosthesis use. These themes, and their associated subthemes, highlight how individuals use their prosthesis and the various factors perceived to act as barriers and facilitators to prosthesis use in everyday life. Conclusions: These findings provide valuable insight into the everyday experiences of individuals with LLA and can be used to implement strategies to optimize prosthesis use.